CD154 Induces Interleukin-6 Secretion by Kidney Tubular Epithelial Cells under Hypoxic Conditions: Inhibition by Chloroquine. (31st January 2020) - Dewitte, Antoine; Villeneuve, Julien; Lepreux, Sébastien; Bouchecareilh, Marion; Gauthereau, Xavier; Rigothier, Claire; Combe, Christian; Ouattara, Alexandre; Ripoche, Jean
Abstract : Inflammation is a major contributor to tubular epithelium injury in kidney disorders, and the involvement of blood platelets in driving inflammation is increasingly stressed. CD154, the ligand of CD40, is one of the mediators supporting platelet proinflammatory properties. Although hypoxia is an essential constituent of the inflammatory reaction, if and how platelets and CD154 regulate inflammation in hypoxic conditions remain unclear. Here, we studied the control by CD154 of the proinflammatory cytokine interleukin- (IL-) 6 secretion in short-term oxygen (O2 ) deprivation conditions, using the HK-2 cell line as a kidney tubular epithelial cell (TEC) model. IL-6 secretion was markedly stimulated by CD154 after 1 to 3 hours of hypoxic stress. Both intracellular IL-6 expression and secretion were stimulated by CD154 and associated with a strong upregulation of IL-6 mRNA and increased transcription. Searching for inhibitors of CD154-mediated IL-6 production by HK-2 cells in hypoxic conditions, we observed that chloroquine, a drug that has been repurposed as an anti-inflammatory agent, alleviated this induction. Therefore, CD154 is a potent early stimulus for IL-6 secretion by TECs in O2 deprivation conditions, a mechanism likely to take part in the deleterious inflammatory consequences of platelet activation in kidney tubular injury. The inhibition of CD154-induced IL-6 production by chloroquine suggests the potential usefulness of this drug as a therapeutic adjunct in conditions associated with acute kidney injury.